Targeting Base Excision Repair in Cancer: NQO1-Bioactivatable Drugs Improve Tumor Selectivity and Reduce Treatment Toxicity Through Radiosensitization of Human Cancer - Starcher, Colton L.; Pay, S. Louise; Singh, Naveen; Yeh, I-Ju; Bhandare, Snehal B.; Su, Xiaolin; Huang, Xiumei; Bey, Erik A.; Motea, Edward A.; Boothman, David A. (Frontiers in Oncology, 2020)
Ionizing radiation (IR) creates lethal DNA damage that can effectively kill tumor cells. However, the high dose required for a therapeutic outcome also damages healthy tissue. Thus, a therapeutic strategy with predictive biomarkers to enhance the beneficial effects of IR allowing a dose reduction without losing efficacy is highly desirable. NAD(P)H:quinone oxidoreductase 1 (NQO1) is overexpressed in the majority of recalcitrant solid tumors in comparison with normal tissue. Studies have shown that NQO1 can bioactivate certain quinone molecules (e.g., ortho-naphthoquinone and β-lapachone) to induce a futile redox cycle leading to the formation of oxidative DNA damage, hyperactivation of poly(ADP-ribose) polymerase 1 (PARP1), and catastrophic depletion of NAD+ and ATP, which culminates in cellular lethality via NAD+-Keresis. However, NQO1-bioactivatable drugs induce methemoglobinemia and hemolytic anemia at high doses. To circumvent this, NQO1-bioactivatable agents have been shown to synergize with PARP1 inhibitors, pyrimidine radiosensitizers, and IR. This therapeutic strategy allows for a reduction in the dose of the combined agents to decrease unwanted side effects by increasing tumor selectivity. In this review, we discuss the mechanisms of radiosensitization between NQO1-bioactivatable drugs and IR with a focus on the involvement of base excision repair (BER). This combination therapeutic strategy presents a unique tumor-selective and minimally toxic approach for targeting solid tumors that overexpress NQO1.